Size effect in correlation-driven charge migration in correlation bands of alkyne chains - Belles, Enguerran; Rabilloud, Franck; Kuleff, Alexander I.; Despré, Victor (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2024)
Correlation-driven charge migration initiated by inner-valence ionization leading to the population of the correlation bands of alkyne chains containing between 4 and 12 carbon atoms is explored through ab initio simulations. Scaling laws are observed, both for the time scale of the charge migration and for the slope of the density of states of the correlation bands. These can be used for predicting the relaxation time scale in much larger systems from the same molecular family and for finding promising candidates for the development of an attochemistry scheme taking advantages of the specificity of the dynamics in the correlation bands of molecules.
Online verfügbar: 27. Dezember 2023
Gesehen am 07.03.2024